2013
DOI: 10.1007/s13762-013-0220-5
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of starch blended polyvinyl chloride films by isolated Phanerochaete chrysosporium PV1

Abstract: The accumulation of plastics in the environment is raising great concerns with respect to long-term environmental, economic and waste management problems. The aim of the present research was to investigate the biodegradability of starch blended polyvinyl chloride films in soil burial and controlled laboratory experiments using selective fungal isolates. Clear surface aberrations as color change and minor disintegration in polyvinyl chloride films were observed after 90 days and later confirmed through scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…Only one paper is available that considered the tuned degradation of PVC when blended with TPS [203]; thanks to the extensive variety of uses for PVC, a complete comprehension of disintegration steps is of fundamental significance from an ecological viewpoint.…”
Section: Hybrid Blends Based On Bio-based and Fossil Fuel-derived mentioning
confidence: 99%
“…Only one paper is available that considered the tuned degradation of PVC when blended with TPS [203]; thanks to the extensive variety of uses for PVC, a complete comprehension of disintegration steps is of fundamental significance from an ecological viewpoint.…”
Section: Hybrid Blends Based On Bio-based and Fossil Fuel-derived mentioning
confidence: 99%
“…Torikai and Hasegawa (1999) reported accelerated photodegradation of PVC when exposed to short-wavelength radiation. However, biodegradation of PVC has been attempted in very few studies (Klrbas et al, 1999;Kaczmarek and Bajer, 2007;Ali et al, 2014;Giacomucci et al, 2019) and shown by very few microorganisms ( Table 2). White rot fungi in the Basidiomycotina were reported to biodegrade low molecular weight PVC when subjected to nutrient (nitrogen, carbon or sulfur) limiting conditions (Klrbas et al, 1999).…”
Section: Polyvyinylchloridementioning
confidence: 99%
“…Significant drift in isolate activity was averted through the use of talc. Consortia composed of a combination of different bacterial strains of Pseudomonas otitidis, Bacillus cereus, and Acanthopleurobacter pedis have the ability to degrade PVC in the environment [64]. These results offer the opportunity to optimization conditions for consortia growth in PVC and use as a treatment technology to degrade large collections of PVC.…”
Section: Polyvinyl Chloridementioning
confidence: 99%